UJI ANTIMITOSIS EKSTRAK ETANOL DAUN SISIK NAGA (Drymoglossum piloselloides [L.] Presl) DENGAN METODE PENGHAMBATAN PEMBELAHAN SEL TELUR Tripneustes gratilla Linn TERFERTILISASI - Rahmawati Rahmawati; Bayu Putra (As-Syifaa Jurnal Farmasi, 2010)
The research concerning antimitotic assay of “Sisik Naga” (Drymoglossum piloselloides [L] Presl) ethanol extract  using Tripneustes gratilla Linn eggs cleavage inhibition method had been conducted. The aim of this study was to evaluate which the extract of that provide higher effect in to inhibit cell division of fertilized sea urchin eggs. Quantivication of division was performed visually by light microscopy by counting the number of cleaveaged and non cleaveaged embryos after an incubation time of  ± 2 hours. If 80 – 100% inhibition of cleavage (IC80-100) occurs at ≤ 16 mg/ml, the compound is considered to be active as antimitotic assay.Key word : Antimitotic, Drymoglossum piloselloides, vinkristin